Determination of the Coefficient of a Semilinear Parabolic Equation for a Boundary-Value Problem with Nonlinear Boundary Condition - Akhundov, A. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study the well-posedness of the inverse problem of determination of the coefficient of a minor term of a semilinear parabolic equation in the presence of a nonlinear boundary condition. The additional condition is given in the nonlocal integral form. A uniqueness theorem and a “conditional” stability theorem are proved.